The Genetic Control of the Compound Leaf Patterning in Medicago truncatula - Mo, Xiaoyu; He, Liangliang; Liu, Ye; Wang, Dongfa; Zhao, Baolin; Chen, Jianghua (Frontiers in Plant Science, 2022)
Two basic types of leaves, simple and compound, are distinguished by the pattern of the distribution of blades on the petiole. Compared to simple leaves comprising a single blade, compound leaves have multiple blade units and exhibit more complex and diverse patterns of organ organization, and the molecular mechanisms underlying their pattern formation are receiving more and more attention in recent years. Studies in model legume Medicago truncatula have led to improved understanding of the genetic control of the compound leaf patterning. This review is an attempt to summarize the current knowledge about the compound leaf morphogenesis of M. truncatula, with a focus on the molecular mechanisms involved in the pattern formation. It also includes some comparisons of the molecular mechanisms between leaf morphogenesis of different model species and offers useful information for the molecular design of legume crops.